Cyberbullying and its relationship with physical, verbal, and relational bullying: a structural equation modelling approach. Issue 3 (16th March 2021) - Johansson, Stefan; Englund, Göran
Abstract: The article focuses on the contentious relation between cyberbullying and physical, verbal, and relational bullying. Drawing on items from the Olweus questionnaire, the study used confirmatory factor analysis and structural equation modelling, and latent factors of bullying were fitted to the data. Different background variables were related to cyberbullying and traditional bullying factors. The results revealed high correlations between physical, verbal, and relational bullying. While the relations between cyberbullying and physical and verbal bullying were modest to moderate, a substantial correlation between cyberbullying and relational bullying was observed (.69). Further, it was noted that the level of anxiety had a stronger relation with the cyberbullying factor, while number of friends was similarly related to all four bullying factors. The implications of the high relation between cyber and relational bullying, as well as their similar association with the covariates, were discussed.